2021
DOI: 10.1021/acscatal.1c02172
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Palladium-Catalyzed Asymmetric Borylative Migration of Enol Perfluorosulfonates: Insights into an Enantiofacial-Selective Transmetalation

Abstract: In 2009, one of our laboratories described a palladium-catalyzed enantioselective borylative migration reaction of heterocyclic enol perfluorosulfonates that provides ready access to optically enriched, synthetically useful dihydropyranyl and dehydropiperidinyl allylic boronates 3 and 4. However, several aspects of the catalytic cycle and the mechanism of enantiomeric induction of the anomalous borylation reaction that produces 3 and 4 remain unknown or ambiguous. Herein, a combination of experimental and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…17−19 It has been reported that the reaction of vinyl triflates with HBpin by palladium catalysis mainly led to allylic borylation. 20,21 Because of these competing reactions, the use of HBpin as an atomefficient boron source in the borylation of esters is underdeveloped and remains chemoselectively challenging. Studies in the field currently focus on the use of precious palladium and rhodium as catalysts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17−19 It has been reported that the reaction of vinyl triflates with HBpin by palladium catalysis mainly led to allylic borylation. 20,21 Because of these competing reactions, the use of HBpin as an atomefficient boron source in the borylation of esters is underdeveloped and remains chemoselectively challenging. Studies in the field currently focus on the use of precious palladium and rhodium as catalysts.…”
mentioning
confidence: 99%
“…The borylation of these esters provides a useful tool in forming vinylated and arylated boron feedstocks, which are currently dominated by using diborons such as B 2 pin 2 and B 2 nep 2 as boron reagents via loss of one boron functionality (Figure a). Compared with diboron-based ester borylation, the use of pinacolborane (HBpin) as a boron source for borylation is of interest because of the atom efficiency, and it usually occurs along with evolution of hydrogen. However, ester scaffolds can be hydrided by the hydrogen or HBpin formed in situ, giving reduced side compounds of de-esterificated olefins, reduced alkanes, arenes, or arenols (Figure b). It has been reported that the reaction of vinyl triflates with HBpin by palladium catalysis mainly led to allylic borylation. , Because of these competing reactions, the use of HBpin as an atom-efficient boron source in the borylation of esters is underdeveloped and remains chemoselectively challenging. Studies in the field currently focus on the use of precious palladium and rhodium as catalysts.…”
mentioning
confidence: 99%